PENGARUH WAKTU FERMENTASI DAN KOMPOSISI LIMBAH ECENG GONDOK (Eichhornia crassipes) UNTUK MENGHASILKAN GAS BIO DENGAN METODE HIDROLISA BASA MENGGUNAKAN NATRIUM HIDROKSIDA (NaOH) - Setiaty Pandia; Pri Hartini (Jurnal Teknik Kimia USU, 2017)
Water hyacinth (Eichhornia crassipes) is a plant that become aquatic waste and its existence has not yet widelyused. The content of cellulose, hemicellulose, and lignin inside it can be used into biogas through fermentation process.The purpose of this research was to determine the effect of alkali pretreatment methods on the yield biogas volume and Total Suspended Solid (TSS) revomal percentage. The study was did by fermentation process the water hyacinth with NaOH concentration of 2,86; 3;4; and 6,67 (M) with water in ratio hyacinth:water 70:30; 50:50; 30:70 and 100:0 (v/v) mixed with cow dug starter in an anaerobic digester batch system of 2,5 L capacity. In this study the highest biogas production at NaOH concentration 6,67 M was in ratio of 70:30 (v/v) with yield biogas volume 506 mL and TSS revomal percentage of 93,23%. Minimum value of gasbio production concentration of NaOH 3M withwater hyacinth:water ratio 30:70 (v/v) generate yield biogas volume 158 mL and TSS revomal percentage of 81,48%.